SISTEMATIZAÇÃO DE PROCEDIMENTOS NA REGULAMENTAÇÃO DOS INSTRUMENTOS DA ÁREA DA SAÚDE : UM ESTUDO DE CASO - Menezes, Cecilia Iolanda Cardoso de (2004)
The objective of this study is to show how legal metrology has evolved, developing techniques and procedures to promote an increase in the quality of measuring instruments at healthy fields. This study also observe all the studied methodology, since the phase of searches to the technical regulamentation project and the develop techniques to minimize the uncertainty until the final implementation of the metrological control in the country. The Medical instruments demand in their metrological control, a higher level of precision and uncertainty, forcing legal metrology to develop techniques and procedures that enable them to grant the result of the measurement, it was on this context, that Inmetro had created standard-laboratories to develop a methodology suitable and consistent with the National Institutes of Metrology from developed countries, reaching this way a new step in industry at a laboratory level. With this study, we intend to show how Inmetro is contributing to the developing of quality of instruments used at medical field, as it grant the interests of society based at the metrological trust required at official economical relations, used in the process of health prevention. The research was developed, also aiming, how metrological control improved the performance of clinical investigations, how much the patient trust on that instruments submitted to the metrological control and how much they doubt of that not regulated yet. And trying also to show the phenomenon occurred before and after the implementation of metrological regulation itself.